The association between unilateral balance and kicking - Ball, K.; Barnes, S. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
Balance is a common coaching cue and technical factor associated with kicking in the football codes. The aim of this study was to compare balance ability and maximal kick performance for the punt kick. Fifteen elite junior Australian Football players performed maximal punt kicks with their preferred and non-preferred legs with foot and ball speed calculated using VICON. Balance ability was assessed unilaterally during three 20 s standing tasks on a force plate using centre of pressure range and medio-lateral force standard deviation. No relationship was found between balance ability and kick performance, similar to soccer kicking. Future work should explore balance in more kick-specific tasks.